PERANCANGAN IDENTITAS VISUAL DALAM DESTINATION BRANDING PASAR BUNGA BRATANG SURABAYA - Ardiansyah, Lucky; Riyanto, Darwin Yuwono; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Writer have done direct observation in place and found that flower markets bratang surabaya not had a logo that is the key important in introduce this place to public .This tourism interested in  market because there is superior products offered .In this research , writer will focus on the process design logo new has become a key factor in the next process .The concept of logo who has been designed namely bloom or from analysis training and keywords .The concept of bloom which means bloom .The philosophy of the logo is a plant starting from seed to flowers that bloom .Said bloom also chosen  because to reflect hope the traders flower markets bratang surabaya in order of place is a choice tourist destinations flower markets superior and was different to kompetitornya .In process of making logo done stage go brainstorm , making alternative visual , sketch logo alternative , logotype election. In addition to the manufacture of the logo , has been designed gsm ( graphic manual standart ) which aims to give an explanation and help users in menggunaan and apply brand identity flower markets bratang .As a broad outline , gsm also took the company profile , brand identity and promotional items .Media promotion made namely in the form of a leaflet , flyer , plastic bag , signage and billboards.Keywords: Identitas Visual, Logo, GSM (Graphic Standart Manual).